Index of Atmospheric Purity (IAP) Related to Potential Ecological Risk Indexes (RI) of Heavy Metals Accumulation in Urban Area - Silprasit, Kun; Rimlumduan, Thipwarin; Phowana, Naphat; Thummajitsakul, Sirikul (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2023)
Heavy metal contamination in protected areas can cause sensitive ecosystems to be at risk. Bioindicators for monitoring heavy metal contamination need to be investigated. The objectives of this study were to determine heavy metal residues in soil in an urban area, and also lichens diversity. Twenty-two sampling plots of 1 km x 1 km size were selected in Nong Saeng sub-district, Pak Phli district in Nakhonayok province, Thailand. Lichens diversity was investigated, and soil samples were collected to analyze the amount of heavy metal residues in the soil. Afterwards, the potential ecological risk indexes (RI) and index of atmospheric purity (IAP) were presented. The results indicated that trace element concentrations in forest (For), urban (Urb) and agriculture (Agr) soils were not significantly different, and that land use type did not affect heavy metal contamination. However, two areas with high RI values of 358.27 and 483.76 were designated as being at considerable ecological risk. These values related to the lowest air quality index in distribution mapping of IAP. The relationship between index of atmospheric purity and potential ecological risk indexes (RI) of heavy metal accumulation in urban area implied that long-range transboundary air pollution may be a source of heavy metals contamination in some areas. The highest RI value related to Hg concentration in low land implied that it was possible that concentrations of heavy metals could have been affected by the discharge of wastewater into the low land, and especially in the study area that had acidic soil.